Pengaruh Penambahan SiO2 dan PTFE Terhadap Respon Termolumi-nesensi TLD CaSO4:Dy - Nuraeni, Nunung; Kartikasari, Dewi; Iskandar, Ferry; Haryanto, Freddy; Waris, Abdul; Hiswara, Eri (Jurnal Matematika dan Sains, 2017)
Thermoluminescence response of TLD CaSO4: Dy with a variation of the addition of SiO2 and PTFE materials has been observed. TLD CaSO4:Dy derived through co-precipitation method and then added by SiO2 and PTFE. Thermoluminescence intensity for CaSO4:Dy added by SiO2 obtained 9.41, 5.32; and 13.93 nC for the temperature at 400 °C, 600 °C and 700 °C. As for CaSO4:Dy with the addition of PTFE obtained 33.10;  336.89; and 1191.11 nC for the temperature at 400 oC temperature, 600 °C and 700 °C. Thermoluminscence intensity for CaSO4:Dy without the addition of SiO2 and PTFE at a temperature of 700 °C is 75.15 nC. There’s a significant increasing in the thermoluminescence intensity on CaSO4:Dy added by PTFE.